Comparing quality of care in non‐profit and for‐profit nursing homes: a process perspective - Chesteen, Susan; Helgheim, Berit; Randall, Taylor; Wardell, Don (Journal of Operations Management, 2005)
AbstractUsing data from a sample of nursing homes, this paper uses an operations centric approach to test the economic hypothesis asserting that quality in non‐profit healthcare entities will exceed quality in for‐profit counterparts [Arrow, K., 1963. Uncertainty and welfare economics of medical care. The American Economic Review, 5, 941–973]. For‐profit healthcare entities face an inherent conflict between providing profits to investors and health welfare to patients. Thus, non‐profit entities exist as a signal and evidence of higher quality services. To date, research examining differences in quality between for‐profit and non‐profit nursing homes has focused on a direct link between outcome quality and non‐profit status. These studies have produced inconclusive or mixed results. We argue that non‐profit or for‐profit status and outcome quality are linked via two intermediate factors, namely process quality and input quality. Consistent with many prior studies, we report no direct link between non‐profit status and outcome quality. However, we report that process quality is indeed higher at non‐profit nursing homes than for‐profit nursing homes, but that input quality is lower. We also examine the association between outcome quality with process and input quality. We report that different aspects of process quality are tied to better outcome quality, but report several notable exceptions. This research provides support for Arrow's hypothesis at the process level and gives insights into the link between process quality, input quality and outcome quality in the nursing home environment.